Perancangan Media Informasi Mengatasi Quarter Life Crisis Dalam Pandangan Islam - Putri, Vina Sri jelita; Rajudin, Rajudin; Bermana, Ary Leo (Relief : Journal of Craft, 2023)
Quarter life crisis is an identity crisis resulting from an individual's unpreparedness in the early adulthood phase. Based on surveys and interviews conducted by the author in Padangpanjang City, data was obtained that 63.70% of early adults experienced a quarter life crisis. The design of an illustrated book on overcoming the quarter life crisis from an Islamic perspective aims to provide information about the quarter life crisis in early adults aged 18-25 years. Data collection methods through the process of interviews, questionnaires, and literature studies, design analysis using 5W+1H analysis, and using a semiotic approach.The visual concept of illustrative book design applies a flat design style with vector techniques. The illustrated book contains information about quarter life crises, the causes of quarter life crises, and how to overcome quarter life crises based on Islamic views. The design stages include brainstorming, keywords, sketches, storyline, color study, typography study. The results of designing information media in the form of an illustrated book address the quarter life crisis from an Islamic perspective. Other media mixes include e-books, posters and supporting media such as banners, t-shirts, quote cards, stickers and instagram feeds.